Analysis of Students' Internal Learning Motivation in Biology Subjects at Madrasah Aliyah Waburense - Sari, Tri Maniarta; Ernawati; Saparuddin; Rahmania Pamungkas (LPPM Press, 2023)
The purpose of this research is to analyze students' internal learning motivation at the Madrasah Aliyah Waburense. The type of research in this research is descriptive quantitative. The data collection technique for this research uses a mixed questionnaire. The subjects of this research consisted of 62 students in grades XI and XII at the Madrasah Aliyah Waburense. This research instrument consists of 4 indicators with 22 statements. The results of research on students' internal learning motivation were obtained; (1) the percentage of indicators of desire and desire to succeed is 68.2%, namely the medium category (2) there are hopes and aspirations for the future, 82.02%, namely the high category (3) shows interest, 54.5%, namely the medium category ( 4) diligent in facing tasks 73.4% high category. Conclusion: Internal learning motivation for classes XI and XII at the Madrasah Aliyah Waburense produces an average percentage of 70.5% in the high category.